2000
DOI: 10.1063/1.1287783
|View full text |Cite
|
Sign up to set email alerts
|

Particle generation and thin film surface morphology in the tetraethylorthosilicate/oxygen plasma enhanced chemical vapor deposition process

Abstract: Particle generation by gas-phase nucleation in the plasma enhanced chemical vapor deposition process and its effects on thin film surface morphology were studied experimentally for a conventional radio frequency plasma reactor using tetraethylorthosilicate (TEOS) vapor and oxygen gases. The particles suspended in the plasma space and deposited on the film were observed simultaneously by in situ laser light scattering methods and an ex situ scanning electron microscopic method. The generated particles were trap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…The formation of nanoparticles by homogeneous nucleation of the intermediate species during the deposition of siloxane coating (using tetraethyl orthosilicate or silane as a precursors) is a common phenomenon (29,(31)(32)(33)(34)(35)(36)(37) in CVD techniques (such as thermal CVD, low pressure PECVD, and atmospheric pressure plasma CVD). This is believed to be due to the excess gas-phase reaction between precursors and process gas.…”
Section: By-product Hazardmentioning
confidence: 99%
“…The formation of nanoparticles by homogeneous nucleation of the intermediate species during the deposition of siloxane coating (using tetraethyl orthosilicate or silane as a precursors) is a common phenomenon (29,(31)(32)(33)(34)(35)(36)(37) in CVD techniques (such as thermal CVD, low pressure PECVD, and atmospheric pressure plasma CVD). This is believed to be due to the excess gas-phase reaction between precursors and process gas.…”
Section: By-product Hazardmentioning
confidence: 99%
“…Some of these efforts include increasing the precursor concentration, the total pressure, and radio frequency (rf) power (Raupp et al 1992;Yi et al 2001). Unfortunately, this leads to the degradation of film properties and the generation of dust particles in the reactor (Fujimoto et al 2000;Setyawan et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the presence of dust particles in a plasma reactor has negligible effects on film properties as long as they are not incorporated into the growing layer. However, it has been shown that dust particles may be deposited into growing films during continuous plasma operation (Fujimoto et al 2000), not at the end of the film deposition when the plasma is turned off (Selwyn et al 1989;Setyawan et al 2003Setyawan et al , 2004.…”
Section: Introductionmentioning
confidence: 99%
“…Fujimoto et al (7) and Dorier et al (18) monitored the distribution of dust particles generated in a parallel-plate radio frequency plasma reactor by introducing a polarized beam-expanded laser and detecting the resulting two-dimensional scattered light distribution. McMillin et al (19) reported two-dimensional laser-based imaging measurements for nanoparticle synthesis using a flame CVD reactor.…”
Section: Introductionmentioning
confidence: 99%